If , , find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
cot x + cot y = 3 0 ⟹ tan x 1 + tan y 1 = 3 0 ⟹ tan x tan y tan x + tan y = 3 0
We were given that tan x + tan y = 2 5
⟹ 3 0 2 5 = tan x tan y
Subtract both sides from 1: ⟹ 1 − tan x tan y = 3 0 5
Divide both side by tan x + tan y = 2 5 ⟹ 1 − tan x tan y tan x + tan y = 2 5 × 5 3 0
But then the LHS is now tan ( x + y ) !
tan ( x + y ) = 1 5 0
By the way, to write tan x please use
for better formatting